A Versatile Class of 1,4,4-Trisubstituted Piperidines Block Coronavirus Replication In Vitro - Sonia De Castro; Annelies Stevaert; Miguel Maldonado; Adrien Delpal; Julie Vandeput; Benjamin Van Loy; Cecilia Eydoux; Jean-Claude Guillemot; Etienne Decroly; Federico Gago; Bruno Canard; Maria-Jose Camarasa; et al. (MDPI AG, 2022)
There is a clear need for novel antiviral concepts to control SARS-CoV-2 infection. Based on the promising anti-coronavirus activity observed for a class of 1,4,4-trisubstituted piperidines, we here conducted a detailed analysis of the structure-activity relationship of these structurally unique inhibitors. Despite the presence of five points of diversity, the synthesis of an extensive series of analogues was readily achieved by Ugi four-component reaction from commercially available reagents. After evaluating 63 analogues against human coronavirus 229E, four of the best molecules were selected and shown to have micromolar activity against SARS-CoV-2. Since the action point was situated post virus entry and lying at the stage of viral polyprotein processing and the start of RNA synthesis, enzymatic assays were performed with CoV proteins involved in these processes. While no inhibition was observed for SARS-CoV-2 nsp12-nsp7-nsp8 polymerase, nsp14 N7-methyltransferase and nsp16/nsp10 2'-O-methyltransferase, nor the nsp3 papain-like protease, the compounds clearly inhibited the nsp5 main protease (Mpro). Although the inhibitory activity was quite modest, the plausibility of binding to the catalytic site of Mpro was established by in silico studies. Therefore, the 1,4,4-trisubstituted piperidines appear to represent a novel class of non-covalent CoV Mpro inhibitors that warrants further optimization and development.